THE INFLUENCE OF GLOBALISATION IN FOREIGN LANGUAGE TEACHING PROCESS - Sadullaeva, A.N. (FAN va JAMIYAT, 2017)
The article deals with the new methods and techniques in teaching and learning process of foreign language education to improve and develop intercultural communicative competence in the target language.